FPGA Implementation of MC-CDMA Wireless Communication System Based on SDR-A Review - Nahar, Ali Kareem; Gitaffa, Sabah A; Ezzaldean, Mohammed Moanes; Khleaf, Hussain K (Review of Information Engineering and Applications, 2017)
Software Defined Radio (SDR) has the flexibility to modify the characteristics of the receiving and transmitting radio device, without physically adjusting the hardware, due to development in the system. Because of the increasing need for wireless communication applications so as to enable consumers to communicate anywhere through information led to the emergence of many communication devices to include the large amount of applications that every one of the devices needs power and thereby increase the total power. This study confirms that the wireless communication system for secured transmit data, fast and inexpensive; can be done by implementing using Partial Reconfiguration (PR) modern technology in FPGA developing based on SDR. The Speed and performance can be improved. The area also can be decreased. The new Xilinx, Vertex Series FPGA, provides the provision of PR. The power consumption can be reduced by applying power reduction techniques in the blocks. The combination of MATLAB (Simulink and M-file) and Simulink HDL Coder offers flexible capabilities for analysis, design; simulation, implementation, and verification. With all these capabilities, in a single system to reduce the time spent tuning for reducing the algorithms and models during rapid prototyping and experimentation and less time on HDL coding.